Impact of Industrial Technology 4.0 In Improving Service Quality and Customer Experience on E-Commerce Platforms: Literature Review - Martasari, Gacelia Weny (International Journal of Social Service and Research, 2023)
With the rise of Industry 4.0 technology, e-commerce platforms have the opportunity to enhance their operations and improve customer experience. Industry 4.0 technology, which includes the Internet of Things (IoT), artificial intelligence (AI), and blockchain, has the possibility to revolutionize e-commerce by enabling personalized, secure, and convenient shopping experiences. The aim of this research is to evaluate the affect of Industry 4.0 technology in improving service quality and customer experience on e-commerce platforms. This article is focused on impact industrial technology 4.0 on e-commerce for data collection. Finding relevant and reputable papers is the first step in creating this article. Then, the search results are sorted by title and abstract. If it is suitable, it is necessary to conduct a literature review and then make a comparison. It was found that industrial technology 4.0 has a significant affect on improving service quality and customer experience on e-commerce platforms. Moreover, the use of industrial technology 4.0 has also improved the personalization of services on e-commerce platforms. With the rapid advancements in technology, e-commerce companies have been able to leverage various tools and solutions to improve their customer service and operational efficiency. By adopting these technologies, e-commerce companies have been able to offer a seamless and personalized shopping experience to their customers, which has, in turn, resulted in higher customer satisfaction rates and increased sales.